1999
DOI: 10.1046/j.1365-2516.1999.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of inhibitors in haemophilia A patients – a review of recent studies of recombinant and plasma‐derived factor VIII concentrates

Abstract: The development of inhibitors to factor VIII or IX is the most serious complication of haemophilia therapy. While early surveys revealed inhibitor prevalences of 3.6-25%, recent studies, especially those using recombinant DNA-derived products, have prompted speculation as to whether ultrapurified products may cause a higher incidence of inhibitors. Although studies of ultrapure rFVIII in previously treated patients have not shown an increased inhibitor risk, in previously untreated patients (PUPs) with severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
173
2
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(188 citation statements)
references
References 43 publications
(73 reference statements)
12
173
2
1
Order By: Relevance
“…Up to 35-40% of subjects with severe hemophilia A develop a factor VIII inhibitor at some stage in their treatment [reviewed by Scharrer et al, 1999 andOldenburg et al, 2000]. Collection of more data on possible factors influencing the inhibitor formation is therefore very important on order to allow correct assessment of inhibitor risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 35-40% of subjects with severe hemophilia A develop a factor VIII inhibitor at some stage in their treatment [reviewed by Scharrer et al, 1999 andOldenburg et al, 2000]. Collection of more data on possible factors influencing the inhibitor formation is therefore very important on order to allow correct assessment of inhibitor risk.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate (factor VIII activity 2-5% of normal) and mild hemophilia A (factor VIII activity 5-30% of normal) occur in about 10% and 30-40% of patients respectively. It has been reported that individuals receiving recombinant factor VIII therapy develop antibodies (s.c. "inhibitors" of factor VIII), leading to autoantibody production against the endogenous protein [reviewed by Scharrer et al, 1999]. The question of correlation between autoimmune response and type of molecular defect in this coagulation factor is still open.…”
Section: Introductionmentioning
confidence: 99%
“…SEAP activity can be monitored in a plasma-based assay that allows longterm surveillance of the gene expression profile without sacrificing the animals. We chose the human gene, and not mouse SEAP, due to the immunogenicity of human SEAP in mice (28,29); this protocol mimics the conditions in gene therapy for congenital protein deficiencies, since proteins responsible for congenital deficiencies are often recognized as foreign by the immune system (30)(31)(32). SEAP expression profiles in mice that received intramuscular electrotransfer of a human SEAP expression plasmid are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of inhibitors in severe hemophilia A is reported to be as high as 20%-52% [1,2] and in hemophilia B is 1.5%-3% [3]. Therapeutic approaches are often based on inhibitor titers as well as response to factor challenge.…”
Section: Introductionmentioning
confidence: 99%